Annual Research Review: Child and adolescent mental health interventions: a review of progress in economic studies across different disorders. (28th February 2014) - Beecham, Jennifer
<x xml:space="preserve">Abstract</x> Background Resources for supporting children and adolescents with psychiatric disorders continue to be scarce. Economics research can identify current patterns of expenditure, and help inform allocation of treatment and support resources between competing needs or uses. Scope and methods The aim was to identify the costs of supporting children and adolescents, the economic impacts of childhood psychiatric disorders in adulthood and any new evidence on the cost‐effectiveness of interventions. An electronic search of databases (including PubMed, Medline and Psychinfo) identified peer‐reviewed journal articles published between 2005 and 2012. Findings Sixty‐seven papers provided data on support and treatment costs now or in the future, or cost‐effectiveness analyses of services. Half the articles came from the United States. Most articles focussed on autism spectrum disorder (ASD; 23 articles), attention deficit hyperactivity disorder (ADHD; n = 15), conduct disorder (CD; n = 7), and anxiety or depression (n = 8). Conclusion Only 14 studies used a cost perspective wider than health care; most included education costs (n = 11), but only five included costs to the justice system. The number of studies estimating costs to the family has increased, particularly for children with autism spectrum disorder (ASD). In the United Kingdom, support costs for children and adolescents with conduct disorder (CD) appear to be lower than for those with attention deficit hyperactivity disorder (ADHD), although for the United States, the opposite may be true. Support costs for children and adolescents with ASD may be higher than both CD and ADHD. However, there were many differences between the samples and the methods employed making comparisons between studies difficult. Outcomes in adulthood include negative impacts on (mental) health, quality of life, public sector services, employment status and income. The evidence base is improving for child and adolescent psychiatric disorders, although only one full cost‐effectiveness analysis was identified since the previous review published in 2012. However, we still do not know enough about the economic implications of support and treatment for specific disorders.